1984
DOI: 10.1002/jcb.240250204
|View full text |Cite
|
Sign up to set email alerts
|

A requirement for cholesterol and its structural features for a human macrophage‐like cell line

Abstract: The lipid requirements of a human macrophagelike cell line were studied. The cells grew only about one generation in a medium supplemented with delipidated serum; during the growth the cholesterol content of the cells was depleted. Growth was restored by including in the medium serum lipids subjected to alkaline hydrolysis or cholesterol. The extent of growth was dependent on cholesterol concentration. No growth was obtained with 5-cholestene, 5-cholesten-3-one, cholesteryl chloride, coprostanol, beta-sitoster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
28
0

Year Published

1987
1987
2005
2005

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 31 publications
5
28
0
Order By: Relevance
“…Thus, Bloch questioned whether the 3␤-OH is mandatory for sterol function or simply arises as a consequence of sterol synthesis. 5-Cholestene, cholestenone, and 3␣-epicholesterol did not support growth of auxotrophic cells, which agrees with previous work in which cholesteryl methylether and 3␣-epicholesterol failed to support growth of a macrophage-like cell line in lipid-depleted medium (34). These findings suggest that an equatorial hydroxyl group at C-3 is essential for mammalian cells.…”
Section: Discussionsupporting
confidence: 90%
“…Thus, Bloch questioned whether the 3␤-OH is mandatory for sterol function or simply arises as a consequence of sterol synthesis. 5-Cholestene, cholestenone, and 3␣-epicholesterol did not support growth of auxotrophic cells, which agrees with previous work in which cholesteryl methylether and 3␣-epicholesterol failed to support growth of a macrophage-like cell line in lipid-depleted medium (34). These findings suggest that an equatorial hydroxyl group at C-3 is essential for mammalian cells.…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, the requirement of a certain amount of cholesterol in addition to 7-dehydrocholesterol to sustain cell growth cannot be ruled out. In agreement with this, we and others have demonstrated that phytosterols may support the proliferation of animal cells, provided that a suboptimal amount of cholesterol is also available (9,14,28).…”
Section: Discussionsupporting
confidence: 87%
“…Thus, the results suggested that 7-dehydrocholesterol contributed to cell proliferation. Supplementing the medium with 7-dehydrocholesterol had been shown previously by others to support the growth of cholesterol-auxotroph cells (9,14). In these cells, however, 7-dehydrocholesterol was efficiently converted to cholesterol; thus, the specific role of that sterol intermediate in cell proliferation could not be evaluated.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Heat-inactivated fetal calf serum (FCS) and basal growth medium RPMI 1640 with 2 mM glutamine were obtained from GIBCO. Delipidated FCS (DLFCS) was prepared as described (11).…”
mentioning
confidence: 99%